Analisis Manajemen Mutu Terpadu (TQM) Dalam Pelayanan Rumah Sakit (Studi Literature) - Ruth Haryanti; Maharanny Wulansari; Aulia Dini Rachmadanti; Febri Diotama; Vip Paramarta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In order to increase customer satisfaction, the hospital is required to maintain and improve the quality of service within the hospital. Efforts to improve the quality of a hospital must be balanced with the implementation of Total Quality Management (TQM) in the optimal health sector by paying attention to all aspects of the hospital. Medical personnel who are agile and skilled in their fields will be very supportive if accompanied by supporting hospital facilities and infrastructure, this can make the hospital known to the wider community because of good service so that the quality of the hospital is not in doubt. For that a hospital must pay attention to quality control management in its own hospital.